Predicting currency markets behavior after scheduled macroeconomic news releases through a trading system approach - Ciet, Giovanni (2013)
This paper analyses the effectiveness of the “Trading the News” phenomena, practiced by many speculators. We examine, through a trading system approach, in the very short time (3 hours), how several macroeconomic news announcements, from 5 different regions (U.S., Euro Zone, U.K., Japan and Australia) are impounded into forex prices. Our goal is to find out whether an exploitable trading pattern exists around these announcements. Profitable results are obtained for the US NFP, the Australian GDP and the UK GDP. Miscellaneous results are obtained for the US Trade Balance, US GDP, Australian CPI and UK Jobless Claim. For the US ISM-Manufacturing, US Retail Sales, Euro GDP, Euro CPI, Japanese GDP, Japanese Tankan, Australian Employment and UK CPI, no exploitable trading pattern is found.